Polifarmácia e sobrevida em nonagenários e centenários do Projeto AMPAL - Rubert, Viviane Maura (2022)
It is expected that the population aging process in Brazil will become even more intense in the coming decades. The elderly, particularly nonagenarians and centenarians, are often affected by multiple morbidities that require the concomitant use of several medications (polypharmacy). Polypharmacy, defined in this work, as the consumption of 5 or more medications, is a reality in the Brazilian population, especially in the elderly, and the main challenge is to qualify health care and ensure the correct and safe use of these medications. The objective of this work was to study the relationship between polypharmacy and survival in nonagenarians and centenarians followed by AMPAL, to identify the frequency of polypharmacy; to observe the possible relationship between polypharmacy and the sociodemographic and clinical characteristics of the participants; to associate the frequency of symptoms related to polypharmacy side effects; to verify the occurrence of potential drug interactions and Potentially Inappropriate Drugs (PMIs) and their relationship with polypharmacy. It is a descriptive longitudinal cohort study with retrospective and prospective data, developed in the AMPAL Project of PUCRS, in the city of Porto Alegre, Rio Grande do Sul – Brazil. A total of 243 long-lived people (nonagenarians and centenarians) were evaluated from June to November 2016. This project was submitted and approved by the PUCRS Research Ethics Committee in October 2020, with CAAE registration: 39384620.0.0000.5336. A total of 1450 medications were identified in use by the study participants, corresponding to 5.9±2.87 medications per participant. Of the total number of elderly people studied, 163 (67%) were on polypharmacy, 80 (33%) without polypharmacy, among which 9 (4% of the total) did not use any medication. A total of 1216 drug interactions were found, of which 115 were major, 912 moderate and 189 minor. The PIMs were classified according to the evidence and recommendation and their frequencies calculated between the groups with and without polypharmacy, 272 PIMs were identified. Participants in polypharmacy had a higher prevalence of PIM in all degrees of evidence, highlighting those with moderate evidence (N=121, 88.3%). In the analysis of survival, polypharmacy and drug interactions were not significantly associated with a higher chance of death. Only MPI use with moderate evidence and strong recommendation was significantly associated with participant survival (p=0.043). We concluded that polypharmacy was prevalent in the nonagenarians and centenarians evaluated and that the use of PIM was a more important predictor of mortality than polypharmacy.